Penerapan Media Poster dalam Meningkatkan Kemampuan Menulis Karangan Deskripsi pada Pelajaran Bahasa Indonesia Siswa Kelas V di SDIT Bunayya Pekanbaru - Indah Ayu Fitriani; Radhiyatul Fithri; Sakban Sakban; Wismanto Wismanto; Deprizon Deprizon; Salman Salman (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
This research was motivated by the low ability to write descriptive essays in Indonesian language lessons for class V students at SDIT Bunayya Pekanbaru. The researcher found a way to solve this problem by applying poster media as an effort to improve the ability to write descriptive essays for class V students. The research method that the researcher used in this research was Classroom Action Research (PTK). This research was carried out in 2 cycles, each cycle having 2 meetings. Each cycle in this research consists of planning, implementation, observation and reflection stages. The data that researchers obtained was then analyzed descriptively. This research involved 30 Sa'ad class V students. Researchers found that the results of teacher and student activities developed significantly in each cycle using poster media. In the first cycle of teacher activities, the results were 53% and 58%. In cycle II teacher activity increased to 66% and 96%. Student activity in cycle one was 34% and 52%. Meanwhile in cycle II it rose to 60% and 79%. The learning outcomes obtained at the pre-cycle stage were 58.10%. After the first cycle was held, the results obtained were 74.43% and the results obtained in the second cycle were 85.07%. The percentage of classical completion in the pre-cycle was 43%, increasing in cycle I by 60% and the percentage obtained in cycle II increased by 90%. Thus, the use of poster media as an effort to improve students' ability to write descriptive essays produces very satisfying results. Keywords: , , and D